Correlation of urticaria activity score in chronic spontaneous urticaria with serum C-reactive protein level and neutrophil/lymphocyte ratio - Akca, Hanife Merve; Tuncer Kara, Kevser (Wiley, 2020)
Chronic spontaneous urticaria (CSU) lacks a specific trigger. The urticaria activity score (UAS) is used to evaluate disease status. Some studies have reported elevated serum levels of high-sensitivity C-reactive protein (hsCRP) in CSU patients, which is correlated with disease severity. The neutrophil/lymphocyte (N/L) ratio is a significant indicator of systemic inflammation. We investigated the potential correlation between serum levels of hsCRP and N/L ratio, as well as urticaria activity, in CSU patients. We included 52 CSU patients treated at the Dermatology Polyclinic of Beysehir State Hospital between August and October 2020, and 50 controls. The 7-day UAS were graded mild, moderate, or intense. We measured N/L ratios, erythrocyte sedimentation rates (ESRs), and the levels of hsCRP, T4, and thyroid-stimulating hormone (TSH) in each group. The anti-thyroglobulin (anti-TG) and anti-microsomal antibody (anti-TPO) levels of CSU patients were also assayed. There were no significant differences in hsCRP, T4, or TSH levels between the groups; however, both the ESR and N/L ratio were significantly higher in CSU patients hsCRP (P = .96), T4 (P = .07), TSH (P = .67), ESR (P < .001), N/L(P < .001). No correlation was evident between the UAS day 7 (UAS7) score and the hsCRP level or the N/L ratio (P = .528 and P = .387). Of all the CSU patients, 19.2% tested positive for anti-TPO and 9.6% were positive for anti-TG; these data were not correlated with the UAS7 (P = 1 and P = .637). Inflammation plays a role in CSU. Although we did not find a correlation between the UAS and either the hsCRP level or the N/L ratio, the ESR and N/L ratio were higher in CSU patients than in controls.
Keywords: autoimmunity; chronic spontaneous urticaria; neutrophil; lymphocyte ratio; urticaria activity score